Analyse de la participation des populations dans la mise en œuvre des projets de développement : cas du projet Accélération des impacts de la recherche climatique du CGIAR pour l’Afrique dans la commune de thiel - Dème, Sadio; Mendy, Gervais; Konaré, Fara (2024)
This study examines the participation of populations during the implementation phase of the CGIAR Climate Research Impact Acceleration Project for Africa (AICCRA). The municipality of Thiel is one of the municipalities involved in the project and is also the area chosen to define this study. The objective of this study is to contribute to the improvement of the project implementation process for a better participation of the population. To carry out this study, To carry out this study, we asked ourselves the question: What is the contribution of the participation of the population in the implementation of the projects? On the basis of this central question, two subsidiary questions were identified to better frame this study. These are: -Is the level of commitment of the population a condition for the success of the projects? -Is the existence of a local framework for consultation a means of facilitating the implementation of projects? This subject has already been dealt with by many authors, international institutions, all with converging opinions on the importance of popular participation in the life stages of projects. It is then, we understand, despite this importance of popular participation, their level of involvement can vary depending on the nature and sector of the project. Based on field surveys, the study shows that the participation of the population was well taken into account during the implementation phase of the AICCRA project. They have been actively involved in all activities carried out at the grassroots. The majority of interviewees would like to see more information and communication between partners and grassroots communities. In addition, the survey revealed that 91.3% of beneficiaries say that the project's objectives support their expectations. However, the appropriation of mobile consulting applications is a problem because of a problem of access to smart phones by many producers. Most producers only have simple telephones. The findings of the research led us to formulate recommendations so that future projects or programs can improve the way they work with grassroots communities and local communities for the success of this important project stage.